Climbing the academic ladder: collaborative autoethnographic narrative of women academicians in Tanzanian higher education institutions - Joyce Nemes; Neema Kumburu (International Journal of Qualitative Research, 2026)
In higher education, few women have managed to climb to senior academic ranks such as Associate Professor and Professor. However, little has been done to document the lived experience of those few women who successfully charted this journey. This collaborative autoethnographic study documents the narratives of two successful women academics in Tanzanian higher education institutions who managed to reach senior academic ranks. The objective was to narrate their personal life experiences of climbing the academic ladder in order to inspire other women academicians with similar aspirations. Guided by feminist theory and resilience theory, the study offers insights that may inspire other women who aspire to advance but face institutional, structural, and social barriers. The study findings revealed that confidence and resilience are fundamental to academic advancement. Additionally, effective time management enables women to balance academic demands and family responsibilities. The findings further revealed that mentorship, collaboration, and professional development are equally critical enablers for women's academic advancement.  While resilience theory affirms participants' adaptive capacity in the face of adversity, feminist theory critically reminds us that individual resilience should not substitute for structural responsibility. The implications are that women’s advancement depends on confidence, time management, mentorship, and institutional reform; resilience must not be allowed to replace institutional accountability.